Cervical Single-Level Pincer Stenosis Causing Myelopathy: A Technical Note and Medium-term Results of a One-Session Microsurgical 360-Degree Treatment - Papavero, Luca; Pietrek, Markus; Marques, Carlos J.; Schmeiser, Gregor (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Aims Single-level circumferential or pincer stenosis (PS) affects few patients with degenerative cervical myelopathy (DCM). The surgical technique and medium-term results of a one-session microsurgical 360-degree (m360°) procedure are presented.Patients Between 2013 and 2018, the data of 23 patients were prospectively collected out of 371 patients with DCM. The m360° procedure comprised a microsurgical anterior cervical decompression and fusion (ACDF), with additional plate fixation, followed by flipping the patient and performing a microsurgical posterior bilateral decompression via a unilateral approach in crossover technique.Results The mean age of the patients was 72 years (range: 50–84); 17 patients were males. The mean follow-up time was 12 months (range: 6–31). The patients filled in the patient-derived modified Japanese Orthopaedic Association (P-mJOA) questionnaire on average 53 months after surgery. One patient received a two-level ACDF. Lesions were mostly (92%) located at the C3/C4 (8/24), C4/C5 (7/24), and C5/C6 (7/24) levels. Functional X-rays showed segmental instability in 10 of 23 patients (44%). All preoperative T2-weighted magnetic resonance imaging (MRI) showed an intramedullary hyperintensity. The median preoperative mJOA score was 13 (range 3), and it improved to 16 (range 3) postoperatively. The mean improvement rate in the mJOA score was 73%. When available, postoperative MRI confirmed good circumferential decompression with persistent intramedullary hyperintensity. There were two complications: a long-lasting radicular paresthesia at C6 and a transient C5 palsy. No revision surgery was required.Conclusion The one-session m360° procedure was found to be a safe surgical procedure for the treatment of PS, and the medium-term clinical outcome was satisfactory.
Keywords: degenerative cervical myelopathy; cervical spondylotic myelopathy; over-the-top decompression; modified Japanese Orthopaedic Association score; pincer stenosis